PENJELIDIKAN MENGENAI TJARA PENJIMPANAN KAJU KARET (Hevea brasiliensis MA) - Balai Rayon dan Selulosa (JURNAL SELULOSA, 1965)
The effect of storage of Hevea brasiliensis MA upon the chemical composition of the wood and the pulp was studied. In this experimenc, the cooking and bleaching conditions were kept constant, but the method of srorage was varied.The growth of blue staining fungi dur"ing srorage was also studied.Logs stored under roof cr in the open air were severely attacked by staining fungi, especially when barked. Storage of the logs under warer or under continuous water spraying markedly inhibited the growth of this fungi.Six month storage showed no clear trend of change in the chemical composition of the wood or the yield of cooking, but the chipping rendement decreased with storage time. The pentosan content and the permanganate number of the unbleached pulp decreased also withstorage time. Especially when stored under water, the permanganate numbers were low.The severe attack of blue stain, resulted in pulp with small black spots and this caused difficulties in the bleaching process.Preliminary investigation upon the suitability of Hevea pulp for rayon making was promising.